The Association between Internet Addiction and Impulsivity among Academicians - Şimşek, Nuray; Zincir, Handan; Özen, Betül; Ceyhan, Özlem (Addicta: The Turkish Journal on Addictions, 2019)
This study seeks to identify the association between academicians’ Internet addiction and impulsivity predispositions of academics and some underlying factors behind it. The study has been conducted with 232 academicians employed at a state university in Turkey’s central Anatolian region. The data have been collected using a participant questionnaire, the Internet Addiction Scale, and the Barratt Impulsiveness Scale. The mean age of the included academicians is 34.91 ± 8.33 years, with 53.4% being male. The participants’ total mean score for Internet addiction is 30.00 ± 8.74. The mean score for impulsivity is 63.58 ± 5.64. The study has found no meaningful association between overall Internet addiction scores with overall impulsivity scores. However, varying levels of association have been observed for all subscales from both scales. The subscales of impulsivity and time spent on the Internet have also been found as predictive factors for Internet addiction. The study has concluded the academicians to have mild degrees of impulsivity and low levels of internet addiction, all sub-dimensions of Internet addiction and impulsivity to be interrelated, and the time spent online to associate with Internet addiction and impulsivity.To
Keywords: Academicians; Addiction; Internet addiction; Impulsivity